Fluorescence lifetime imaging of upper gastrointestinal pH in vivo with a lanthanide based near-infrared τ probe. Issue 15 (14th March 2019) - Ning, Yingying; Cheng, Shengming; Wang, Jing-Xiang; Liu, Yi-Wei; Feng, Wei; Li, Fuyou; Zhang, Jun-Long
Abstract : Lanthanide complex was successfully applied in the design of pH-responsive NIR τ probe for quantitative in vivo imaging. Abstract : Time-resolved fluorescence lifetime imaging (FLIM) in the near-infrared region of 900–1700 nm not only allows a deep tissue penetration depth but also offers the unique benefit of the quantitative visualization of molecular events in vivo and is independent of local luminescence intensity and fluorophore concentration. Herein, we report the design of a wide-range pH sensitive molecular probe based on Yb 3+ porphyrinate. The Yb 3+ probe shows increasing NIR emission and lifetime with p K a values of ca. 6.6 from pH 9.0 and 5.0 and also displays an elongated lifetime from ca. 135 to 170 μs at lower pH values (5.0–1.0) due to aggregation and reduced exposure to water at low pH values. Importantly, the probe is able to monitor a wide range of in vivo gastrointestinal pH values in mice models and the potential applications in imaging-guided gastrointestinal diagnostics and therapeutics were revealed. This study shows that lifetime contrast is important for preclinical imaging; lanthanide complexes could be successfully used in the design of stimuli-responsive NIR τ probes for advanced in vivo imaging.